2007
DOI: 10.1111/j.1540-8175.2007.00472.x
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Primary Cardiac Lymphoma: Analysis of the Role of Echocardiography in Early Diagnosis

Abstract: Primary Cardiac Lymphoma (PCL) is defined as a non-Hodgkin's lymphoma involving only the heart and/or pericardium. Diagnosis of this rare disease is particularly difficult due to its nonspecific clinical manifestations. In this review the role of echocardiography in the early diagnosis of PCL is assessed, moreover we report an improvement in the outcome of PCL related to increased availability and utilization of echocardiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
32
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 18 publications
1
32
0
Order By: Relevance
“…There have been only 3 cases of T-cell origin described in the literature. 3 Park et al described a 10-year-old boy with an anaplastic cardiac T-cell lymphoma with freedom of disease at 12-month follow-up after receiving surgical tumor resection and chemotherapy. 4 The other 2 adult male patients with PCL of T-cell origin died within 1 month after diagnosis because of malignant arrhythmias.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…There have been only 3 cases of T-cell origin described in the literature. 3 Park et al described a 10-year-old boy with an anaplastic cardiac T-cell lymphoma with freedom of disease at 12-month follow-up after receiving surgical tumor resection and chemotherapy. 4 The other 2 adult male patients with PCL of T-cell origin died within 1 month after diagnosis because of malignant arrhythmias.…”
Section: Discussionmentioning
confidence: 98%
“…11 Faganello et al reported a complete remission rate of 71% in patients receiving early and effective treatment, whereas Ikeda et al obtained complete remission in only 15 of 40 patients. 3,7 A role for heart transplantation in patients with malignant cardiac tumors has never been established as results were uniformly unfavorable. Hence, our patient's success may lead to new treatment strategies to overcome this dreadful disease.…”
Section: Discussionmentioning
confidence: 99%
“…TTE has a sensitivity of 55–60% for primary cardiac tumors and TEE has a sensitivity of 97–100%. The sensitivity of cardiac magnetic resonance imaging is superior to that of CT (90–92 vs. 71–73%) (4,7). In 92% of PCL cases reported, the right heart chambers were involved, predominantly the RA.…”
Section: Discussionmentioning
confidence: 99%
“…Reported complete remission rates have ranged from 38% to 71%, illustrating the limited knowledge of this disease [6, 11]. Risk factors for poor prognosis include immunocompromised state, extracardiac disease, left ventricular involvement, and the absence of arrhythmia.…”
Section: Discussionmentioning
confidence: 99%